2018
DOI: 10.3390/polym10060608
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Bamboo Fiber Reinforced Epoxy Composites

Abstract: Bamboo fibers demonstrate enormous potential as the reinforcement phase in composite materials. In this study, in order to find suitable NaOH concentration for bamboo fiber treatment, bamboo fibers were treated with 2 wt.%, 6 wt.% and 10 wt.% NaOH solutions for 12 h, respectively. We determined that 6 wt.% NaOH treated bamboo fibers were optimal for the fabrication of bamboo fiber composites by single fiber tensile test, single fiber pull-out test, Fourier transform infrared spectroscopy (FTIR), and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(146 citation statements)
references
References 47 publications
(59 reference statements)
8
116
0
Order By: Relevance
“…To overcome the problem of phase's compatibility, the lignocellulosic fillers are usually chemically modified to improve the interface's compatibility thus enhancing adhesion. For example, Kai Zhang et al . produced epoxy composites reinforced with bamboo fibers and concluded that the use of unmodified fibers resulted in poor interfacial adhesion between fibers and epoxy resin matrix, mainly due to the hydrophilic moieties on the surface of the fibers.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the problem of phase's compatibility, the lignocellulosic fillers are usually chemically modified to improve the interface's compatibility thus enhancing adhesion. For example, Kai Zhang et al . produced epoxy composites reinforced with bamboo fibers and concluded that the use of unmodified fibers resulted in poor interfacial adhesion between fibers and epoxy resin matrix, mainly due to the hydrophilic moieties on the surface of the fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the hydrophilic nature of natural fibres and hydrophobic nature of polymer matrices, low compatibility between the fibre-matrix leads to poor wettability of the natural fibres to the polymer matrices. Poor interfacial adhesion between the natural fibres and polymer matrices degrades the mechanical properties and the moisture resistance of the composites, thus limits the further application of natural fibre composites (Akhtar et al 2016;Punyamurthy et al 2017;Qian et al 2015;Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…% NaOH solution at room temperature for 24 and 48 h was performed on coir fibres. Epoxy resin was used as the polymer matrix as it has excellent mechanical properties, chemical resistance and electrical insulation (Zhang et al 2018). The structural properties (SEM and FTIR analyses), thermal degradation and water absorption ability of the coir fibres composites was further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The peak of the curve clearly defines that more amount of energy is absorbed and it doesn't allow the impactor to penetrate inside the composite. The presence of filler basalt powder provides additional strength to the flax fiber in the time of application of impact force about of 1755 N. The improved interfacial bonding between the basalt powder and the polyester resin will exhibits this kind of responses in the time of sudden load applications [27]. In figure C severe damages were noted for the composite C and the peak of the curve clearly indicates that the composite does not absorb the application of load.…”
Section: Low Velocity Impact Response On Flax Fiber/basalt Powder Commentioning
confidence: 96%